The Impact of Board Structure on Corporate Performance: an Empirical Study on Listed Companies in China - Mu, Wenxiu (2014)
The topic of corporate governance, as an important research field enjoys great popularity in many countries. In some rapidly growing markets like China, investors have strong desires to improve the governance mechanism. In recent years, a great many of researches on this topic have been made. However, these studies and researches seem to be not so successful and have not obtain a certain key finding due to various uncertain factors such as the different management approaches and methods adopted by different companies, rapid changes of the market and so on. Board of directors, as the significant monitors for management have strong powers, play a key role in the company.